2016
DOI: 10.1016/j.snb.2016.05.123
|View full text |Cite
|
Sign up to set email alerts
|

Detection and sizing of single droplets flowing in a lab-on-a-chip device by measuring impedance fluctuations

Abstract: International audienceThis paper is devoted to the evaluation of the electrochemical noise technique consisting in measuring the fluctuations of the electrolyte resistance (ER) between two metallic electrodes immerged in a conductive electrolyte to detect and characterize single particles circulating in a microfluidic device, without the help of optical measurements that require good visibility of the detection region. Numerical simulations were performed with the finite element method to study the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Electrical impedance spectroscopy has been utilized in combination with microfluidics as an emerging label-free technology with good efficiency and sensitivity [19,20] to differentiate cell populations [2124], single droplets [25], and diseased blood cells [26,27] as well as to monitor cellular pathological conditions [28]. This method is based on cellular dielectric properties [19], size and composition [26,29,30] and does not require any biochemical and fluorescence markers.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical impedance spectroscopy has been utilized in combination with microfluidics as an emerging label-free technology with good efficiency and sensitivity [19,20] to differentiate cell populations [2124], single droplets [25], and diseased blood cells [26,27] as well as to monitor cellular pathological conditions [28]. This method is based on cellular dielectric properties [19], size and composition [26,29,30] and does not require any biochemical and fluorescence markers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, capacitive sensing using interdigital electrode geometry has been demonstrated for the detection of 900 μm water-in-oil emulsions produced by flow focusing42. Yakdi et al reported detecting and sizing oil droplets greater than 50 μm in diameter generated by a T-junction by measuring impedance fluctuations 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the electrode system for nonadhesion cells is the same as that for adhesion cells (see Figure a–h). ,, First, the electrode systems (see Figure a,b) designed for cell population measurement cannot accurately detect many cell biophysical properties such as cell number and cell size, because those electrode systems generally measure the changes in solution resistance produced by the release of ionic metabolites from live cells (see Figure c) . Therefore, they may be used for cell metabolism measurement.…”
Section: Design Of Impedance-based Cell Sensing Devicesmentioning
confidence: 99%
“…Sensing electrodes can be designed on both sides of a microchannel (see Figure 3d) 42 or only on one side of a microchannel (see Figure 3e). 46 Those two electrode systems can realize cell counting; however, they cannot extract any biophysical information on individual cells, such as cell size, membrane capacitance, and cytoplasm conductivity, because cell position in the microchannel (>cell size) greatly affects the measurement of nonadhesive cells.…”
mentioning
confidence: 99%